Synthesis and Characterization of Graphite Composite Foams for Oil Spill Recovery Application - Vincenza Brancato (Journal of Composites Science, 2020)
The aim of this paper is the synthesis and characterization of a composite silicone foam filled with expanded graphite (EG) for oil spill recovery applications. The EG foams were obtained using a foaming slurry consisting of a mixture of siloxane compounds as the matrix with an EG filler. The effect of the filler content’s performance on an innovative composite silicone-based foam was investigated. All the obtained samples exhibited an open cell morphology. Each foam was evaluated in four commonly used oils (kerosene, pump oil, naphtha and crude oil). Additionally, kinetics was studied in order to investigate the physical, chemical and mass transport mechanisms that act during the absorption phenomenon and uptake evolution of the contaminants. Foam filled with 3% of EG exhibited the highest absorption capacity, particularly with light oils kerosene and virgin naphtha (854 and 1016 wt.%, respectively). Furthermore, the kinetic study showed that pseudo-second order mechanisms better fitted the composite absorption performances, suggesting that the oil sorption into EG filled polydimethylsiloxane (PDMS) foams could be related to chemisorption mechanism. The results evidenced a good oil sorption capability and water/oil selectivity indicating this class of materials as a potentially applicable material for oil spill remediation.